Diagnosis and management of Barrett esophagus: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Weusten, Bas L. A. M.; Bisschops, Raf; Dinis-Ribeiro, Mario; di Pietro, Massimiliano; Pech, Oliver; Spaander, Manon C. W.; Baldaque-Silva, Francisco; Barret, Maximilien; Coron, Emmanuel; Fernández-Esparrach, Glòria; Fitzgerald, Rebecca C.; Jansen, Marnix; Jovani, Manol; Marques-de-Sa, Ines; Rattan, Arti; Tan, W. Keith; Verheij, Eva P. D.; Zellenrath, Pauline A.; Triantafyllou, Konstantinos; Pouw, Roos E. (Endoscopy, 2023)
MR1 ESGE recommends the following standards for Barrett esophagus (BE) surveillance:– a minimum of 1-minute inspection time per cm of BE length during a surveillance endoscopy– photodocumentation of landmarks, the BE segment including one picture per cm of BE length, and the esophagogastric junction in retroflexed position, and any visible lesions– use of the Prague and (for visible lesions) Paris classification– collection of biopsies from all visible abnormalities (if present), followed by random four-quadrant biopsies for every 2-cm BE length.Strong recommendation, weak quality of evidence.MR2 ESGE suggests varying surveillance intervals for different BE lengths. For BE with a maximum extent of ≥ 1 cm and < 3 cm, BE surveillance should be repeated every 5 years. For BE with a maximum extent of ≥ 3 cm and < 10 cm, the interval for endoscopic surveillance should be 3 years. Patients with BE with a maximum extent of ≥ 10 cm should be referred to a BE expert center for surveillance endoscopies. For patients with an irregular Z-line/columnar-lined esophagus of < 1 cm, no routine biopsies or endoscopic surveillance are advised.Weak recommendation, low quality of evidence.MR3 ESGE suggests that, if a patient has reached 75 years of age at the time of the last surveillance endoscopy and/or the patient’s life expectancy is less than 5 years, the discontinuation of further surveillance endoscopies can be considered. Weak recommendation, very low quality of evidence.MR4 ESGE recommends offering endoscopic eradication therapy using ablation to patients with BE and low grade dysplasia (LGD) on at least two separate endoscopies, both confirmed by a second experienced pathologist.Strong recommendation, high level of evidence.MR5 ESGE recommends endoscopic ablation treatment for BE with confirmed high grade dysplasia (HGD) without visible lesions, to prevent progression to invasive cancer.Strong recommendation, high level of evidence.MR6 ESGE recommends offering complete eradication of all remaining Barrett epithelium by ablation after endoscopic resection of visible abnormalities containing any degree of dysplasia or esophageal adenocarcinoma (EAC).Strong recommendation, moderate quality of evidence.MR7 ESGE recommends endoscopic resection as curative treatment for T1a Barrett’s cancer with well/moderate differentiation and no signs of lymphovascular invasion.Strong recommendation, high level of evidence.MR8 ESGE suggests that low risk submucosal (T1b) EAC (i. e. submucosal invasion depth ≤ 500 µm AND no [lympho]vascular invasion AND no poor tumor differentiation) can be treated by endoscopic resection, provided that adequate follow-up with gastroscopy, endoscopic ultrasound (EUS), and computed tomography (CT)/positrion emission tomography-computed tomography (PET-CT) is performed in expert centers.Weak recommendation, low quality of evidence.MR9 ESGE suggests that submucosal (T1b) esophageal adenocarcinoma with deep submucosal invasion (tumor invasion > 500 µm into the submucosa), and/or (lympho)vascular invasion, and/or a poor tumor differentiation should be considered high risk. Complete staging and consideration of additional treatments (chemotherapy and/or radiotherapy and/or surgery) or strict endoscopic follow-up should be undertaken on an individual basis in a multidisciplinary discussion.Strong recommendation, low quality of evidence.MR10 a ESGE recommends that the first endoscopic follow-up after successful endoscopic eradication therapy (EET) of BE is performed in an expert center.Strong recommendation, very low quality of evidence.b ESGE recommends careful inspection of the neo-squamocolumnar junction and neo-squamous epithelium with high definition white-light endoscopy and virtual chromoendoscopy during post-EET surveillance, to detect recurrent dysplasia.Strong recommendation, very low level of evidence.c ESGE recommends against routine four-quadrant biopsies of neo-squamous epithelium after successful EET of BE.Strong recommendation, low level of evidence.d ESGE suggests, after successful EET, obtaining four-quadrant random biopsies just distal to a normal-appearing neo-squamocolumnar junction to detect dysplasia in the absence of visible lesions.Weak recommendation, low level of evidence.e ESGE recommends targeted biopsies are obtained where there is a suspicion of recurrent BE in the tubular esophagus, or where there are visible lesions suspicious for dysplasia.Strong recommendation, very low level of evidence.MR11 After successful EET, ESGE recommends the following surveillance intervals:– For patients with a baseline diagnosis of HGD or EAC:at 1, 2, 3, 4, 5, 7, and 10 years after last treatment, after which surveillance may be stopped.– For patients with a baseline diagnosis of LGD:at 1, 3, and 5 years after last treatment, after which surveillance may be stopped.Strong recommendation, low quality of evidence.